Caller ID – Whose Privacy Is It, Anyway? - Ferguson, Kenneth G. (Journal of business ethics, 2001)
Caller ID or CND (Calling Number Display) is an internationally-available telecommunication service first introduced into the United States about ten years ago. Caller ID utilizes a new form of technology which enables telephone subscribers to identify the numbers (and/or names) of callers before picking up their telephones. This service has been widely assailed as an invasion of the caller's right to anonymity, a right which allegedly subsists as an important component of the caller's right to privacy. However, if privacy is defined from the perspective of the British philosopher John Stuart Mill, it can be argued that, even though anonymity is in fact an implication of genuine privacy, placing an unsolicited telephone call does not constitute a private act. Indeed, many callers who routinely block their numbers from Caller ID display units (such as telemarketers and telecharities) falsely assert a right to place anonymous calls in order to expedite their own intrusion into the privacy of others. This conclusion will be strengthened by contrasting anonymous telephone calls with the much more legitimate appeals to anonymity made by Usenet bulletin boards in cyberspace.